Managerial Openness dalam Organisasi Pemerintah Non-Kementerian: Studi Deskriptif pada Bank Pemerintah Non-Kementerian - Puji Gufron Rhodes; Nisa Indah Pertiwi (BADAN PENERBIT STIEPARI PRESS, 2025)
This study was conducted with employees at a non-ministerial government-owned bank. Managerial openness refers to how willing supervisors are to listen to ideas, input, and feedback from their team members. Data were collected from 102 employees who had worked at the bank for at least one year. The survey was distributed in person and returned by those who voluntarily agreed to participate. The results revealed that 62.8% of employees felt that managerial openness was present but not yet optimal, 17.6% considered it to be high, and 19.6% perceived it as still low. These findings suggest that while some efforts have been made by managers to be more open, many employees still feel that their voices are not truly being heard. In the context of a government bank where formal structures and hierarchies are often strong this becomes a critical point. When leaders create space for open and respectful dialogue, employees tend to feel more confident in sharing their ideas and concerns.